EFEKTIVITAS OFLOXACIN TETES PADA PENGOBATAN OTITIS MEDIA AKUT STADIUM PERFORASI BERDASARKAN JENIS KELAMIN DAN USIA DI RUMAH SAKIT UMUM MADANI MEDAN - MUHAMMAD YUSUF KHALID; ANNISA . (JURNAL ILMIAH MAKSITEK, 2021)
Otitis Media is an inflammation of part or all of the mucosa of the middle ear, Eustachian tube, mastioid antrum and mastoidcells. At the stage of Acute Otitis Media Perforation Stadium occurs perforation of the tympanic membrane and secretessecretions. The usual medicine given to overcome this problem namely Ofloxacin with ear drops preparation and is used inall genders and ages. Several studies suggest differences in effectiveness giving drugs based on sex and age so thatresearchers are interested in knowing the difference. To assess the effectiveness of ofloxacin drops in the treatment ofperforated acute otitis media against gender and age. Observational analysis with cross sectional design. The research datawere obtained from secondary data using medical records of patients with Acute Perforated Otitis Media who received dropsof Ofloxacin treatment who seeking treatment at the Medan Madani General Hospital for the period 2019-2020.. Then theanalysis was carried out using the Chi Square test. The results of the Chi Square test showed that there was no significantdifference in the effectiveness of using ofloxacin drops in the treatment of acute perforated otitis media patients with maleand female sex with a value of P = 0.550 (> 0.05) and there was no significant difference in effectiveness. On the use ofOfloxacin drops in the treatment of patients with Otitis Media Acute Perforation Stage for age with a value of P = 0.128(0>0.05). The effectiveness of using Ofloxacin drops in the treatment of Acute Perforation Stage Otitis Media was nodistinctive difference in gender and age.